If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5y + 5 = -2(4y + 8) Reorder the terms: 5 + -5y = -2(4y + 8) Reorder the terms: 5 + -5y = -2(8 + 4y) 5 + -5y = (8 * -2 + 4y * -2) 5 + -5y = (-16 + -8y) Solving 5 + -5y = -16 + -8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '8y' to each side of the equation. 5 + -5y + 8y = -16 + -8y + 8y Combine like terms: -5y + 8y = 3y 5 + 3y = -16 + -8y + 8y Combine like terms: -8y + 8y = 0 5 + 3y = -16 + 0 5 + 3y = -16 Add '-5' to each side of the equation. 5 + -5 + 3y = -16 + -5 Combine like terms: 5 + -5 = 0 0 + 3y = -16 + -5 3y = -16 + -5 Combine like terms: -16 + -5 = -21 3y = -21 Divide each side by '3'. y = -7 Simplifying y = -7
| 7-5x+1= | | 11x-9=11x+1 | | 2x^4+4x^2-6=0 | | -11.5x=92.0 | | -1.5=-15 | | k+50=125 | | 2+3a+9a= | | y+13=63 | | x^2+17x+21x=4x-1 | | x-35=40 | | 473-39= | | 7-3d-8+d= | | 437-39= | | -3(3b+3)+(10b-6)=0 | | 5x^3+4x^2-61x+12=0 | | x^3-6x^2+8=0 | | 1-(x)(x)=0 | | 8a+4-6a-5a= | | 7(3n+4)=9(9n+5)+6 | | 6(9-x)=5(x+6) | | x-9=-41 | | 5.2q-5.3-4.7q=0.5q-4.1 | | -x-24=-7-3x-3 | | 6y-7-5y=14 | | 12x-11=85 | | 12(3x+6)=18 | | -3x=y-12 | | x=0.52(2n+15) | | -5x+55=5+5x | | 3Y-3=18-4Y | | Z+m=6 | | 14x^5+7x^3=2x |